INVESTASI DI PASAR MODAL SYARIAH DALAM KAJIAN ISLAM - Anna Nurlita (Kutubkhanah, 2015)
Capital Market Act 1995 does not distinguish between the conventional capital market with the Islamic capital market. This raises some questions about the concepts and principles of Islamic capital markets, as well as the trading mechanism in the Islamic capital market. To answer these questions, this study aims to determine the difference between the conventional capital market based on the principles of Islamic capital markets and capital market concepts, application of capital market trading mechanisms in conventional versus Islamic capital market, and the meaning of investment according to Islamic Shari'a. To explain the purpose of this research, engineering studies and documents through a literature study will describe the rules concerning the capital market both conventional and Islamic. Based on the research results can be explained that the conventional capital market concepts and principles are not much different from the Islamic capital market. The only difference is the emphasis on the type of issuer and the securities to be traded in accordance with Islamic principles. While trade execution procedure between the conventional capital market and Islamic capital markets are no different, namely by using JATS (Jakarta Autometed Trading System). The difference lies only in contracts used in the transaction. Meanwhile, the investment can’t be separated from the Islamic Shari'a because investment is allowed in Islam, however, in contrast to speculative investments.